2003
DOI: 10.21608/ejabf.2003.1799
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Some Antibiotics on Biochemical Changes in Plasma of the Sharptooth Catfish Clarias Gariepinus.

Abstract: C iprofloxacin (15 mg/kg body weight), amoxycillin (50 mg/kg body weight) and ampicillin (80 mg/kg b. wt.) administered orally to male sharptooth catfish Glorias gariepimts 3 times, every 72 hours intervals. Plasma samples were taken for three successive days after the last dose the most important results were : t) Plasma glucose levels were significantly elevated in fish administered ciprofloxacin and amoxycillin at the 3 days studied and ampicillin at the 3 rd day. In contrast, hypoglycemia observed in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
4
3
0
Order By: Relevance
“…niloticus reflected a significant increase in levels of urea, while in combination between them the level of urea not differed compared to the control (I, A). In agreement, Rizkalla et al, (2003) observed that the level of urea increased due to CFX. As such, our observation may show the combination of NSO and CFX does not affect the urea level compared to use both of them individually as well as this combination does not have a deleterious effect on creatinine levels.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…niloticus reflected a significant increase in levels of urea, while in combination between them the level of urea not differed compared to the control (I, A). In agreement, Rizkalla et al, (2003) observed that the level of urea increased due to CFX. As such, our observation may show the combination of NSO and CFX does not affect the urea level compared to use both of them individually as well as this combination does not have a deleterious effect on creatinine levels.…”
Section: Discussionsupporting
confidence: 85%
“…Each of NSO and CFX in O. niloticus reflected a significant increase in levels of urea, while in combination between them the level of urea not differed compared to the control (I, A). In agreement, Rizkalla et al, (2003) observed that the level of urea increased due to CFX.…”
Section: Discussionsupporting
confidence: 78%
“…The recommended dose also raised the plasma glucose significantly on day 21. The results of the elevated glucose with doses and the extended dosage gave conclusive indications that OA medication is a chemical stressor similar to those observed in Clarias gariepinus exposed to quinolone antibiotics (Rizkalla et al, 2003). Though the glucose decreased significantly on day 21 POD, the levels were still significantly higher than on day 0.…”
Section: Discussionsupporting
confidence: 65%
“…Kotak et al (1994); Bury et al (1997) and Kopp and Hetesa (2000) reponed that exposure of rainbow trout, brown trout and juvenile carp to the liver toxin cyanobacterial caused a dramatic increase in the enzymes ALT and AST released into the bloodstream (an indication of severe liver trauma). Rizkalla el aL (2003) observed an increase in plasma ALT and AST of Clarias gariepinus resulting from liver injury caused by antibiotics and ALT was more sensitive to antibiotic administration. Siau and Ip (1987) mentioned-that AST was at least eight times more active than ALT in the liver of different fish species.…”
Section: Effect Of C Perfringens Infection On Some Parameters In 0 Nmentioning
confidence: 85%
“…kidney and intestine of moribund striped bass. Also 'Rizkalla et al (2003) mentioned that the elevated plasma ALP activity in Clarias gariepinus treated with three antibiotics corresponded to an inflammatory reaction of the bile ducts. From the present study, it is concluded that the virulent bacteria cause a high mortality rate among the cultured fish while the drastic effect of the mild bacteria is inflected more on the fish physiological status and as a consequence decreases the farm production.…”
Section: Effect Of C Perfringens Infection On Some Parameters In 0 Nmentioning
confidence: 99%